A star-shaped D-π-A small molecule based on a tris(2-methoxyphenyl)amine core for highly efficient solution-processed organic solar cells - Min, Jie; Luponosov, Yuriy N.; Solodukhin, Alexander N.; Kausch-Busies, Nina; Ponomarenko, Sergei A.; Ameri, Tayebeh; Brabec, Christoph (Journal of Materials Chemistry C, 2014)
A new star-shaped D-π-A small molecule, 2,2′,2′- nitrilotris[(3-methoxy-4,1-phenylene)-2,2′-bithiene-5′, 5-diyleth-1-yl-1-ylidene]trimalononitrile N(Ph(OMe)-2T-DCN-Me), with high efficiency potential for photovoltaic applications was synthesized. Introducing a soluble tris(2-methoxyphenyl)amine (TPA-MeO) core unit can significantly improve the solubility of star-shaped small molecules without negatively impacting intramolecular conjugation and intermolecular solid state arrangements. Solution-processed organic solar cells based on a blend of N(Ph(OMe)-2T-DCN-Me) and PCBM show an initially high power conversion efficiency of over 4% under simulated AM 1.5. © the Partner Organisations 201
Keywords: Engineering controlled terms: Molecules; Stars; Synthesis (chemical) High power conversion; Organic solar cell; Photovoltaic applications; Small molecules; Solution-processed; Star-shaped Engineering main heading: Solar cells